Photo-oxidation of whey proteins: Molecular markers of modification. (March 2017) - Dyer, Jolon M.; Clerens, Stefan; Thomas, Ancy; Callaghan, Chris; Deb-Choudhury, Santanu; Haines, Stephen
Abstract: Oxidative damage significantly affects the food industry, with progressive modification of protein foods and ingredients altering structure, shelf-life, digestibility, nutritional value and function. A redox proteomic damage scoring system was applied to profile and track protein primary level photo-oxidative modification in UVB-irradiated bovine milk whey proteins, lactoferrin and β-lactoglobulin. Lactoferrin oxidation increased significantly after ultraviolet B (UVB) exposure, with the redox score increasing from 0.38 in the control to 1.00 in the irradiated sample. β-lactoglobulin oxidation also increased significantly, from a relatively high baseline redox score of 1.07 in the control to 1.67 in the irradiated sample. A potential marker peptides set for tracking photo-oxidation in milk whey proteins was characterised, with six lactoferrin and four β-lactoglobulin peptides identified. This is anticipated to be of significant utility in monitoring and tracking relative levels of modification, and therefore exposure to oxidative insult, in dairy products through processing, storage, and retail and consumer handling.